Well-being and innovativeness: motivational trigger points for mutual enhancement. Issue 5 (1st June 2015) - Honkaniemi, Laura; Lehtonen, Mikko H.; Hasu, Mervi
Abstract : Purpose: – This paper focuses on employees' motivation to participate in innovation at the workplace. The best arguments to persuade employees to renew their work were searched. According to the expectancy theory (Vroom, 1964), a plausible link must be perceived for a motivational state to arise. The paper investigated the perceptions that employees, team-leaders and directors have about the relationships between innovativeness and well-being. Design/methodology/approach: – The data consisted of thematic interviews with 14 persons from knowledge- and labour-intensive organisations in the public service sector. Data included material from directors, team-leaders and front-line workers. The theoretical model of Huhtala and Parzefall (2007) was applied to analyse perceptions about links between well-being and innovativeness. Findings: – Results indicated that all eight possible links between well-being and innovativeness were perceived as plausible. The most common views were that high innovativeness connects to high well-being and vice versa. Additionally, low well-being was seen to decrease innovativeness. All organisational levels of knowledge- and labour-intensive organisations shared these views. More specifically, the interviewees shared the view that participating in innovation activities gives the employee opportunities to influence one's work, which in turn leads to well-being. Another commonly shared perception was that if employees were encouraged and praised for their efforts, innovativeness would increase. These provide plausible arguments for leaders to persuade employees to participate. Practical implications: – Practical advice about effective arguments for motivating employees is given: tell them that innovativeness is desired for, time and space is allocated for innovations, the amount of change will be managed, and the innovation activities present an opportunity to have voice. Originality/value: – This paper shows potential motivational trigger points for enhancing the interaction between well-being and innovation.